Religiosity and entrepreneurship behaviours - Gursoy, Dogan; Altinay, L.; Kenebayeva, A. (Pergamon, 2017)
© 2017 Elsevier Ltd This study investigates the impacts of entrepreneurs’ religiosity on their values and on the relationship between their values and entrepreneurial behaviours by examining the differences between practicing Muslim entrepreneurs and non-practicing Muslim entrepreneurs. Relationships between values and religiosity are examined within an integrative framework of Schwartz's value theory. Findings suggest that religion plays a critical role in shaping individuals values and their entrepreneurial behaviours. Practicing Muslim entrepreneurs have more respect for, commitment to and acceptance of the religious and traditional customs and ideas compared with those non-practicing Muslim entrepreneurs. On the other hand, non-practicing Muslim entrepreneurs have more independent thoughts and actions when it comes to choosing, creating and exploring compared with those practicing Muslim entrepreneurs. Furthermore, non-practicing Muslim entrepreneurs are more likely to seek for worldly pleasures and sensuous gratification compared with those practicing Muslim entrepreneurs.